(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Curcumin Extract in curcumet capsules has antioxidant, anti-inflammatory, antiviral and antifungal actions. Curcumin exerts anti-inflammatory activity by inhibition of a number of different molecules that play an important role in inflammation. curcumin is effective in reducing post-surgical inflammation. curcumin helps to prevent atherosclerosis by reducing the formation of bloods clumps. Curcumin inhibits the growth of Helicobacter pylori, which causes gastric ulcers and has been linked with gastric cancers. Curcumin can bind with heavy metals such as cadmium and lead, thereby reducing the toxicity of these heavy metals. This property of curcumin explains its protective action to the brain. Curcumin acts as an inhibitor for cyclooxygenase, 5-lipoxygenase and glutathione S-transferase. It is a common spice, known mostly for its use in Indian dishes as a common ingredient in curries and other ethnic meals. Turmeric has also been used for centuries in Ayurvedic medicine, which integrates the medicinal properties of herbs with food. This extraordinary herb has found its way into the spotlight in the west because of its wide range of medicinal benefits.This article reviews the current available scientific literature regarding the effect of Curcumet capsules as an effective supplementation for various life style disorders & as an effective potent Antioxidant.